2011
DOI: 10.1111/j.1365-2052.2010.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of MC3R gene polymorphisms with body weight in the red fox and comparative gene organization in four canids

Abstract: There are five genes encoding melanocortin receptors. Among canids, the genes have mainly been studied in the dog (MC1R, MC2R and MC4R). The MC4R gene has also been analysed in the red fox. In this report, we present a study of chromosome localization, comparative sequence analysis and polymorphism of the MC3R gene in the dog, red fox, arctic fox and Chinese raccoon dog. The gene was localized by FISH to the following chromosome: 24q24-25 in the dog, 14p16 in the red fox, 18q13 in the arctic fox and NPP4p15 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…The comparative analysis of the coding sequence of the MC1R gene in four canids indicated its high evolutionary conservatism. The observed sequence homology (97.9-99.1%), including a shorter phylogenetic distance between dog and Chinese raccoon dog than between dog and the foxes, was similar to that reported earlier for the MC3R (Skorczyk et al 2011), MC4R (Skorczyk et al 2007 and several other genes (for review see Switonski et al 2009). A relatively large number of missense polymorphisms in the dog and red fox may result from a longer breeding history of these species and/or larger total number of the genotyped animals.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The comparative analysis of the coding sequence of the MC1R gene in four canids indicated its high evolutionary conservatism. The observed sequence homology (97.9-99.1%), including a shorter phylogenetic distance between dog and Chinese raccoon dog than between dog and the foxes, was similar to that reported earlier for the MC3R (Skorczyk et al 2011), MC4R (Skorczyk et al 2007 and several other genes (for review see Switonski et al 2009). A relatively large number of missense polymorphisms in the dog and red fox may result from a longer breeding history of these species and/or larger total number of the genotyped animals.…”
Section: Resultssupporting
confidence: 88%
“…The observed sequence homology (97.9–99.1%), including a shorter phylogenetic distance between dog and Chinese raccoon dog than between dog and the foxes, was similar to that reported earlier for the MC3R (Skorczyk et al . ), MC4R (Skorczyk et al . , ) and several other genes (for review see Switonski et al .…”
Section: Resultsmentioning
confidence: 99%
“…An extensive genome scanning search for polymorphisms associated with dog body size revealed the presence of a SNP haplotype, spanning the IGF1 gene, which was characteristic of small dog breeds . In the MC3R gene among numerous polymorphisms no missense mutation was found in the dog and the 3 canidsthe red fox, arctic fox and Chinese raccoon dog [Skorczyk et al, 2011]. However, one silent substitution and 1 substitution in 3 -UTR appeared to be associated with body weight in red foxes.…”
Section: Discussionmentioning
confidence: 91%
“…Although these three mutations do not change amino acid sequences, synonymous SNPs can affect in vivo protein folding, mRNA stability (Duan et al, 2003), and Values with different superscript letters (a, b) within the same line differ significantly at P < 0.05. splicing (Pagani et al, 2005), and consequently affect function as well as gene expression and phenotype Sauna et al, 2007). Synonymous mutations in MC3R are closely associated with daily weight gain, body weight, and feed efficiency in pigs and red foxes (Skorczyk et al, 2011;Weisz et al, 2011); further studies are required in order to investigate how SNPs affect variations in these traits. BMTs and MQTs are quantitative traits controlled by multiple genes (Boukha et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the porcine MC3R, two silent single-nucleotide polymorphisms (SNPs) have been detected, and are significantly related to daily weight gain (Weisz et al, 2011). Furthermore, extensive studies on the MC3R gene in the chicken, dog, red fox, and Chinese raccoon dog have revealed variable levels of polymorphism (Sharma et al, 2008;Skorczyk et al, 2011), and association studies conducted on chickens and red foxes have revealed significant relationships with body weight, carcass weight, feed efficiency, and abdominal fat mass. However, few studies have been conducted on MC3R and bovine BMTs and MQTs.…”
Section: Introductionmentioning
confidence: 99%